A visão de ciência de Mário Schenberg: intuição e imaginação nas origens das ideias científicas - Souza, Aroldo Quinto de (2012)
The objective of this research is to discuss the role of imagination in the discovery /transformation of scientific ideas. For this primarily conducted a survey in order to characterize the imaginative process in scientific activity, then, we seek a scientist whose ideas about the importance of imagination, allowed us to continue the work as proposed initially. Analyzing in this context, we would not have trouble finding scientists whose work scientific would serve as object of study, however, we chose the Physical Mário Schenberg, because analysis of their conceptions about the process of creation of scientific ideas, allowed us to understand that Schenberg was a scientist what, demonstrating a lot of clarity of their role not only in science but in the society of his time, developed a thought and a vision of science that is distanced of the standard vision, a science inscribed in the nature of rational knowledge, in which the introduction of a new idea by an strict act of imagination or intuition, it would be unthinkable. We expect this work to contribute to the continuity of discussion about the actual paper that imagination and intuition played, and, certainly, still play in the creation of scientific ideas